ACCOUNTING BOOKKEEPING AND MARKETING GOVERNANCE WITH MOBILE MARKETING IN CARVING CRAFT INDUSTRY - Putri, Putu Yudha Asteria; Mada, I Gede Nyoman Carlos W.; Dewi, I Gusti Ayu Ratih Permta (Universitas Pahlawan Tuanku Tambusai, 2024)
The Padas stone industry is known in Bali as home decoration and Hindu religious shrines in Bali. This craft has a story from a long history and infrastructure about the civilization of the Balinese people. Until now, along with the development of science and technology, Padas stone crafts have also experienced development. Keramas Village, as a craft center, is the name of a village in Gianyar Regency. Geographically, Keramas Village is a lowland village. In the Keramas neighborhood, in general the majority of residents make their living in the arts and crafts sector. However, in running their business, some craftsmen still face dominant obstacles. The obstacles faced include business management that still does not fully implement management principles. Governance, starting from product design, financial management and the entire HR (employee) work process, is carried out by the owner and manager. This PKM provides assistance with Padas stone crafts in the form of financial management and management to preserve Padas stone crafts in Bali